Nine black robes : inside the Supreme Court's drive to the right and its historic consequences - Biskupic, Joan (William Morrow, an imprint of HarperCollinsPublishers, 2023)
With unparalleled access to key players, a CNN senior legal analyst and Supreme Court expert provides an urgent and inside look at the history-making era of the Supreme Court during the Trump and post-Trump years, including its reversal of Roe v. Wade.